Extended Literature Review of Implementing a Strategic Change in Health Care System: The Importance of Leadership and Change Readiness - Alharbi, Fawziya Salem (British Journal of Healthcare and Medical Research, 2025)
An extended literature review conducted in relation to initiate a management change in a healthcare organisation, to enhance nurse’s engagement in quality meetings by implementing a specific strategic change related to leadership importance and change significant change readiness. Aim: To develop awareness of issues likely to enhance employee engagement level towards the quality meeting in X organisation, with a particular reference to leadership. Methodology: Various literature, journal, articles, reports and books reviewed to accomplish the aim of this paper, by considering leadership necessities and change readiness.A significant strategy implemented with leadership support to implement the change in the organisation and to enhance nurses’ engagement in quality meetings. Findings: Leaders are important to develop a considerable change within the organisation, by increasing the change readiness and managing the change through different techniques such as policy and guidelines, workshops and training and changing the culture. Recommendations: Provide extensive training to the leaders to enhance their skills. Develop training about quality to increase nurse’s awareness about the quality concept and provide policies related to the quality. Overcome the issues that interfere with nurse’s engagement in quality meetings.